Pengelolaan Hama Terpadu (PHT) Kutu Kebul, Kutu Daun (APHIDS) dan THRIPS Pada Tanaman Cabai Keriting (Capsicum annuum Linn.) - Riston Hatorangan Sitorus; Wilyus Wilyus (Jurnal Media Pertanian, 2023)
The study was carried out to find outthe effect of applying IPM model in controlling whiteflys, aphids and thrips on curly chili plants (Capsicum annuum L.). The research was conducted in Research and Teaching Farm of AgricultureFaculty, University of Jambi in March-July 2022.  Tere were two treatments: 1) Implementation IPM model (planting corn plants as pestsbarrier around chili plants, planting basil plants as pests repellents between chili plants,spraying botanical pesticides based on pest monitoring),and 2) Convensitional pest control (spraying synthetic pesticides intensively). Each treatment was 100 m away and repeated 7 times placed in once block. Observation variables were the populations of whiteflys, aphids and thrips;theplants attacked by those pests;and the plants attacked by viruses. The results showed that the treatment IPM model had a significant effect in suppressing population of whiteflys, aphids and thrips; as well as suppressing plants attacked by those pests and the plants attacked by viruses.IPM model by planting corn plants as pests barrier around chili plants, planting basil plants as pests repellents between chili plants, spraying botanical pesticides based on monitoring was much better in ctrollingwhiteflys, aphids and thrips on curly chili plants.